Complementary and integrative medicine in the higher education of physical education: advances, challenges, old and new debates - Barboni, Viviana Graziela de Almeida Vasconcelos; Carvalho, Yara Maria de (Saúde e Sociedade, 2021)
The introduction of Complementary and Alternative Medicine (CAM) into undergraduate health programs has been unsatisfactory and this is not different in Physical Education. This study proposes an analysis of the presence of this theme in higher education in Physical Education at Brazilian federal and state public universities, aiming to elucidating the challenges, gaps and advances that the area faces. Thus, an analysis of 172 curriculum grades for undergraduate courses in the area was conducted. The programs of 52 disciplines in CAM and the research lines of Postgraduate Programs and Research Groups led by professionals in the area were also analyzed. The results show little insertion of the theme in the graduation curricula, and when present, they occur in elective and technical subjects, without dialogues with the Brazilian Unified Health System (SUS). There was still a small participation of the area in scientific production and post-graduation in CAM.